ASSESSMENT OF HYPOCHONDRIASIS IN MEDICAL AND DENTAL STUDENTS - Mahnoor Moiz Khan; Khizra Rehman; Shoaib Khan; Saima Akram Butt; Waqas Khan Jadoon; Madiha Pirvani; Sanam Tauheed (ziauddin University, 2024)
ABSTRACT   Background: Anxiety and depression are considered as an important mental health indicators in the community. Medical undergraduates face several emotional, mental and physical stresses during the academic years. Researches indicate that medical students experience a large amount of psychological pressure due to work required in a competitive environment, extreme working hours, examination stress, large amount of information to seek, lack of social life, responsibility of human welfare. Anxiety and depression ranks fourth as the leading cause of disability globally. Several studies suggest high prevalence depression and anxiety among medical students with distress levels consistently higher than general population. The objective was to assess the level of hypochondriasis among the medical and dental student from first year to final year.   Methodology: A cross sectional survey was conducted amongst the students of medical and dental college at Ziauddin University. The study included total 404 students from both disciplines, a pre-structured questionnaire "The Illness Altitude Scale- IAS" was given to the students after validation. SPSS version 17 was used for data analysis and p value >0.05 was considered significant.   Results: Of the total (n=450) 404 students completed the questionnaire. The average mean age was 22.05±2.6. Of the total (n=164) dental students, 10 students had mild, 83 moderate and 71 had severe hypochondriasis. Among (n=240) medical students, 13 had mild, 153 moderate and 74 had severe hypochondriasis.   Conclusion: These finding confirms the presence of hypochondriasis among the medical and dental undergraduate students, which increases from mild to severe from initial to final years.